(untitled) (Journal of the College of Basic Education, 2025)
The research aimed to to identify the level of some physiological connotations at rest time (metabolism at rest (RMR), the number of heart rates at the time of rest Physiological connotations, and the adoption of technology measuring these physiological connotations as indicators to evaluate the periodic review of planning and implementing the methods of training used for young players in basketball, and the descriptive curriculum in the survey style of the research community represented by its borders of the basketball league players in the Baghdad Governorate for the Sports Mass (2024/2023) represented by both clubs Participation in this league, which is (electrical industries, housing, Salish, Air Force, Popular Mobilization, Civil Defense) of (72) players, all of whom were deliberately chosen in a comprehensive inventory by (100 %) of this society, and the researcher adopted physiological measurement technology in a system Italian Fit Mate Pro is a Bluetooth for each player by surveying them with this system. and then the data of each of these physiological connotations and their arrangement in an upward metabolism test time and descending to my heartbeat tests and breathing rate in order to derive standards of standard evaluation of the level of some physiological connotations at the time of rest at the research Sam The conclusions and recommendations are that it helps the objective measurement by adopting physiological sport technology trained to obtain a quantitative evidence that enables him to set standard levels for each player to evaluate the training curriculum followed with them based on the criteria derived from the results of some physiological connotations at the time of rest (metabolism at rest (RMR), and the number of heartbeat HR REST, and the breathing rate time (RF)), and the coach’s knowledge of the level of physiological connotations (metabolism at rest (RMR), the number of heartbeat at rest (HR REST), and the breathing rate at rest (RF)) helps) Basketball players have to support their planning for their training according to their capabilities in these indicators, It is necessary to provide a Fitmate pro device system for each club and prepare an assistant medical staff or physiological test specialists in it to obtain quantitative data with high accuracy and objectivity that helps coaches evaluate their training curricula in this collective game.